ON BECOMING A PASSIONATE LAWYER (The Pretoria Student Law Review, 2021)
As a lecturer, however, I have come to the realisation that the hallowed halls of academia have, of late, become hollow with the apparent lack of interest in the law by many law students. Many of them have become disengaged, disinterested, and dare I say, disenchanted with the study of law. Very few ‘live and study law deliberately’ and certainly only the exceptional students ‘suck out the marrow of the law’! Why is this so? Why has the study of law apparently become institutionalised, monotonous and, ultimately, mediocre? What has happened to the ‘starry-eyed’-first year student who enrolled for law ‘in the pursuit of justice and the truth’, who, fuelled by an undaunted idealism, wanted to study law ‘for the greater good of society’? This idealism seemingly evaporates over the years of the study of law, and many senior law students are reduced to credit-collecting, minimalist survivors who resist attendance of lectures, the research of case law and materials, lamenting about time tables, and only thriving on the memorising of previous test and examination-papers. Why, on a dramatic note, have they become so disillusioned? The answer in my opinion is simple: it is a matter of passion (or rather the lack thereof)!
Keywords: lack of interest; study of law; students; passion